NCMP-01. COMPARISON AND QUANTITATION OF HISTOPATHOLOGY ABNORMALITIES IN SURGICALLY RESECTED CEREBRAL RADIATION NECROSIS AS COMPARED WITH RECURRENT BRAIN TUMOR FOLLOWING RADIATION. (5th November 2018) - Rogers, Lisa; Tatsuoka, Curt; Machtay, Mitchell; Badve, Chaitra; Tiwari, Pallavi; Prasanna, Prateek; Sloan, Andrew; Selman, Warren; Cohen, Mark
Abstract: BACKGROUND The histologic features of radiation necrosis (RTN), a dysregulated repair process following brain radiation, have not been defined and distinguished from recurrent brain tumor (RBT) following brain radiation therapy. The aim of this study is to compare the type and severity of histologic characteristics of tissue specimens containing predominantly or totally RTN versus predominantly or totally RBT obtained at imaging progression after brain tumor radiation. METHODS Subjects were identified from brain tumor pathology reports of resected recurrent/progressing MRI enhancing lesions following brain radiation at UHCMC from 2004--2013. RTN was defined by < 20% active tumor, the remainder radiation treatment effects. RBT was defined by >80% active tumor. (Mixed cases were excluded). H & E slides were reviewed for 30 characteristics including vascular pathologies, necrosis, tumor features, tissue reaction, inflammatory infiltrate, blood products, and dystrophic calcification. Localization in grey/white matter and leptomeninges was noted. Each characteristic was graded in quartiles by one neuropathologist. The profile was compared with original tumor when available. RESULTS 66 patients were identified, 40 RBT (25 glioma, 15 metastasis) and 26 RTN (14 metastasis, 12 glioma). We identified significant differences in frequency and severity of zonal/geographic necrosis in RTN versus RBT in glioma (p=.002) and metastasis (p=.012) and nonsignificant difference in severity of vascular hyalinization in RTN versus glioma RBT (p=0.44). Demyelination was of borderline significance. Fibrinoid vascular necrosis, vessel wall thickening, and RT astrocytes were not significantly different in RTN versus RBT of either tumor type. In some cases, necrosis and vascular pathology were similar to pretreatment histology. CONCLUSION A multivariable assessment of histologic characteristics may assist neuropathologists in interpretation of surgically resected lesions following brain tumor radiation therapy, especially when pretreatment tumor is available for comparison. We will present imaging correlations with pathology findings. Grant support CTSC UL1TR000439